VIRTUAL REALITY GAME DEVELOPMENT AND OPTIMISAION WITHEXTERNAL HAND MOTION SENSOR (PANGEEA, 2025)
This paper presents the development and optimization of a virtual reality game controlled by an external hand motion sensor (Leap Motion) mounted on VR glasses. The study demonstrates hand recognition without a handheld controller, implemented in a Unity-based project with a horror-themed random maze. It compares three control approaches (wrist movement, joystick, and hand-gesture-based virtual keystrokes) and discusses occlusion culling optimization to improve performance. The results show near-native response times and improved stability over a default OpenVR integration, with an emphasis on low-latency and reliable hand-tracking. The work also covers mounting and integration considerations and suggests future directions for recognizing additional gestures.
Keywords: VR; Virtual Reality; Hand Gesture sensor; Leap Motion